Nitric oxide in the breath of bottlenose dolphins: Effects of breath hold duration, feeding, and lung disease. Issue 1 (14th May 2013) - Yeates, Laura C.; Carlin, Kevin P.; Baird, Mark; Venn‐Watson, Stephanie; Ridgway, Sam
Abstract Breath analysis, including measurement of nitric oxide (NO), is a noninvasive diagnostic tool that may help evaluate cetacean health. This is the first report on the effects of breath hold duration, feeding, and lung disease on NO in dolphin exhaled breath. Three healthy dolphins were trained to hold their breath for 30, 60, 90, and 120 s and then exhale into an underwater funnel. Exhaled NO values from 157 breath samples were compared among three healthy dolphins by breath hold time and after fasting and feeding. Exhaled NO values were also measured in two dolphins with pulmonary disease. NO in dolphin breath was higher compared to ambient air; healthy dolphins had higher NO concentrations in their breath after feeding compared to after overnight fasting; and there were no significant differences in exhaled NO levels by breath hold duration. A dolphin with Mycoplasma‐associated pneumonia and chronic gastrointestinal disease had higher postprandial exhaled NO levels compared to healthy controls. This study demonstrates, contrary to previous publications, that dolphins exhale NO. Given the high standard deviations present in exhaled breath NO values, future studies are needed to further standardize collection methods or identify more reliable samples (e.g., blood).